2017
DOI: 10.1103/physrevfluids.2.034604
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic dynamics of large-scale structures in a turbulent wake

Abstract: The dynamics of a 3D bimodal turbulent wake downstream a square-back Ahmed body are experimentally studied in a wind-tunnel through high-frequency wall pressure probes mapping the rear of the model and a horizontal 2D velocity field. The barycenters of the pressure distribution over the rear part of the model and the intensity recirculation are found highly correlated. Both described the most energetic large-scale structures dynamics, confirming the relation between the large-scale recirculation bubble and its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…The bluff body is a 0.7 scale of the original Ahmed body Ahmed et al (1984): it is L = 0.731 m long, H = 0.202 m high and W = 0.272 m wide, as described in Varon et al (2017). The rear part of the model is a square-back geometry with sharp edges leading to a massive separation of the flow and to the creation of a large 3D recirculation bubble over the rear part of the model.…”
Section: Ahmed Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…The bluff body is a 0.7 scale of the original Ahmed body Ahmed et al (1984): it is L = 0.731 m long, H = 0.202 m high and W = 0.272 m wide, as described in Varon et al (2017). The rear part of the model is a square-back geometry with sharp edges leading to a massive separation of the flow and to the creation of a large 3D recirculation bubble over the rear part of the model.…”
Section: Ahmed Bodymentioning
confidence: 99%
“…Recently, it was shown that the large-scale slow-time oscillations behaves like a high dimensional chaotic system with a well-defined strange attractor (Varon et al, 2017). This result was obtained through the analysis of the timeseries of the coordinate of the barycenter of the wall-pressure field measured over the rear vertical part of the model.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They are not a reconstruction of a particular periodic behaviour, as the succession of the bi-stable states seems to be a weak chaotic process (Varon et al 2017). Nevertheless, they still provide insights into how the wake evolves between states.…”
Section: Characterisation Of the Symmetric Statementioning
confidence: 99%
“…In these conditions, it was found that the characteristic time between switches can be estimated as T l ∼ 10 3 H∕V ∞ , where V ∞ is the freestream velocity. The succession of reflectional symmetry breaking states was initially thought to behave like a stationary Markov chain, although more recent findings from Varon et al (2017) suggest that the low-frequency dynamics may be considered as a weak chaotic process with two attractors. In Grandemange et al (2013b), it is also shown that this long period motion yields an unsteady side force that was inferred to be responsible for part of the drag.…”
Section: Introductionmentioning
confidence: 99%